Governança em ambientes de inovação para o desenvolvimento regional sustentável: o Santa Maria tecnoparque - Cruz, Anderson Cougo da (2016)
The creation of a technology park can be a consequence of the development of a region. It can also be the agent for this to occur. By studying the mechanisms and contingency management, it is common to come across the situation of adapting organizations, culture factors and society and better use of natural resources. One cause of this awakening and recognition of the problem of misuse of such resources, tends to occur because most finitude of consciousness of those. In this scenario, the regional development process meets the sustainable thinking, making that contemplate not only the economic dimension but also social and environmental, to result in greater local impact and then global. As the advancement of studies in the area of sustainability, technology centers - innovation environments - it is provide a governance founded on this ideology. Moreover, they are sites already recognized as agents for the enhancement of the sustainable development of a territory. In this study, the object is the Santa Maria Tecnoparque (Santa Maria, RS, Brazil), being grounded in these principles and composed of a board of academic, business and government spheres. Exploratory and descriptive, qualitative study, which aimed to analyze how existing governance in Santa Maria Tecnoparque influence for Sustainable Regional Development of the city. Thus, there was the opportunity of access to the park's environment, see how involved, managers and entrepreneurs are thinking about their practices, to the park is regional development agent. It observed that SM Tecnoparque is experiencing difficulties, but with better governance practices, tends to become a successful innovation environment and thus an agent of sustainable regional development, as stated in its mission.